2022
DOI: 10.3389/fpls.2022.949541
|View full text |Cite
|
Sign up to set email alerts
|

Tomato salt tolerance mechanisms and their potential applications for fighting salinity: A review

Abstract: One of the most significant environmental factors affecting plant growth, development and productivity is salt stress. The damage caused by salt to plants mainly includes ionic, osmotic and secondary stresses, while the plants adapt to salt stress through multiple biochemical and molecular pathways. Tomato (Solanum lycopersicum L.) is one of the most widely cultivated vegetable crops and a model dicot plant. It is moderately sensitive to salinity throughout the period of growth and development. Biotechnologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 240 publications
1
35
0
Order By: Relevance
“…26 An explanation for the few statistically significant differences observed comes from the developmental phase of the plants investigated here that were in their adult stage: salinity usually results in stronger effects during seed germination and early seedling growth. 26 The adult stage was chosen because it was established to perform spraying on the fully developed first pair of true leaves. Effects of the Phyto-Couriers on Gene Expression.…”
Section: ■ Results and Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…26 An explanation for the few statistically significant differences observed comes from the developmental phase of the plants investigated here that were in their adult stage: salinity usually results in stronger effects during seed germination and early seedling growth. 26 The adult stage was chosen because it was established to perform spraying on the fully developed first pair of true leaves. Effects of the Phyto-Couriers on Gene Expression.…”
Section: ■ Results and Discussionmentioning
confidence: 87%
“…Tomato is moderately sensitive to salt stress and puts in place adaptive mechanisms toward this abiotic stressor . An explanation for the few statistically significant differences observed comes from the developmental phase of the plants investigated here that were in their adult stage: salinity usually results in stronger effects during seed germination and early seedling growth . The adult stage was chosen because it was established to perform spraying on the fully developed first pair of true leaves.…”
Section: Resultsmentioning
confidence: 99%
“…The GO analysis showed that DEPs in molecular function were enriched mainly in the entries for membranes, organelles, binding, cellular processes, metabolic processes, and stress responses ( Figure S4 ). Salt stress results in many molecular changes in plants ( Guo et al., 2022 ). Among the cellular components, the entries for cells, cell parts, organs and membranes were enriched with more DEPs, indicating that salt stress triggered dynamic regulation of cellular components.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, salt stress disrupts chloroplasts and mitochondria, leading to a reduction in photosynthesis and the breakdown of large amounts of glucose required for normal growth and development. Salt stress leads to an imbalance in the ion content of the cell, and many redox reactions are affected ( Guo et al., 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Salinization reduces plant growth and crop productivity by regulating osmotic pressure, ion exchange, material transport in tomato ( Guo et al., 2022 ). MiRNAs have been found to play crucial regulatory roles in tomato resistance to salt stress.…”
Section: The Role Of Mirnas In Abiotic Stresses In Tomatomentioning
confidence: 99%